Digital literacy level of prospective teacher students in the 4.0 industrial revolution era - Hartati, Tri Asih Wahyu; Lestari, Purwaning Budi; Istiawan, Nurcholis; Darmawan, Ericka (Univeritas Papua, 2024)
Digital literacy is an essential competency needed in the Industrial Revolution 4.0 era, driven by rapid technological advancements. This study aims to analyze the level of digital literacy of prospective teacher students in facing the Industrial Revolution 4.0 era, focusing on students’ demographics, namely age, gender and length of study. Survey method was administered in this study, involving 120 prospective teacher students from Universitas Insan Budi Utomo as the respondents. The data were collected through a questionnaire of 1-5 Likert scale, which included questions assessing students' digital literacy levels. The findings of this study portrayed data on students' digital literacy levels according to demographics (gender, age, and length of study). In general, the digital literacy level of Insan Budi Utomo University students is known to be in the “fairly good” category with an average score of 3.14 for the knowledge aspect and 3.20 for the usage aspect. The results of this study are recommended as a reference for designing learning experiences that empower digital literacy, supporting students in becoming more digitally proficient.